4G LTE (Long Term Evolution) Network Optimization Using Physical Tuning Methods for the Kubu Gulai Bancah Area. - Muhammad Naufal Az Zaky; Zurnawita Zurnawita; Amelia Yolanda (LEMBAGA KAJIAN PEMBANGUNAN PERTANIAN DAN LINGKUNGAN (LKPPL), 2025)
This study aims to optimize the 4G LTE network in the Kubu Gulai Bancah area, West Sumatra, which is a suburban area with weak signal and unstable internet speed challenges. The main problem identified is that the network quality is not yet optimal based on Telkomsel's Key Performance Indicator (KPI) parameters, as well as the need for an appropriate optimization method to improve this quality. The research methodology involves a drive test using the G-NetTrack Pro application on a Redmi Note 13 Pro 5G smartphone to collect RSRP, SINR, and Throughput data. The collected data is then processed using MapInfo for visualization and analysis, and simulated with Atoll software for optimization planning. Initial drive test results showed that while RSRP was mostly in the “very good” category (55%) and Throughput was predominantly ‘good’ (84%), SINR was still dominated by the “poor” category (56%). Optimization was performed using physical tuning, specifically adjusting the tilt and re-azimuth of the antenna at Site Campago Ipuh 2, Sector 1, with an azimuth change from 0° to 65°. After optimization, the bad spot area for RSRP decreased from 13.2% to 10.89%, and for SINR from 14.1% to 13.21%. The good category for Throughput also increased from 30.5% to 32%. This optimization successfully improved signal coverage quality and network performance significantly.